A History of the Case Study Sexology, Psychoanalysis, Literature - Lang, Birgit (Manchester University Press, 2017)
This volume tells the story of the case study genre at a time when it became the genre par excellence for discussing human sexuality across the humanities and the life sciences. A History of the Case Study takes the reader on a transcontinental journey from the imperial world of fin-de-siècle Central Europe to the interwar metropolises of Weimar Germany, and to the United States of America in the post-war years. Foregrounding the figures of case study pioneers, and highlighting their radical engagements with the genre, the work scrutinises the case writing practices of Sigmund Freud and his predecessor sexologist Richard von Krafft-Ebing; writers such as Leopold von Sacher-Masoch and Weimar intellectuals such as Erich Wulffen. There result new insights into the continuing legacy of such writers, and into the agency increasingly claimed by the readerships that emerged with the development of modernity-from readers who self-identified as masochists, to conmen and female criminals.